PROFICIENCY IN READING, WRITING AND TRANSLATION SKILLS: ESP ASPECT - Kavaliauskienė, Galina; Kaminskienė, Ligija (Vertimo studijos, 2017)
This paper addresses, first, students‘ attitudes to reading, writing and translating in English as a foreign language for specific purposes and, second, to self-evaluation of proficiency in these skills. The problem of translation is closely confined to the two skills of reading and writing. The investigation has aimed at gathering verbal and written data from the students at university for making informed decisions to ensure effective language learning.Translation trains the reader to search (flexibility) for the most appropriate words (accuracy) to convey what is meant (clarity).A. Duff